Reduction of liquid metal heat losses is the key to the efficiency of foundry production - I. Tahetsi; V. V. Korobeynikov; S. S. Tkachenko (Литьë и металлургия)
One of the metallurgists’ problems is that the reducing of liquid metal heat losses is diffi ult, which is directly related to energy savings and the finished products quality. It is shown that the greatest heat losses of metal occur in the ladle from the moment it is released from the furnace to pouring. Methods and equipment for saving energy costs (gas, electricity) during smelting and casting of foundry alloys are given. Special attention is paid to the need to create stands for high‑quality heating of ladles, lining of ladles and the use of ladles with lids and thermal furnaces of the new generation of the company «TACHTECH‑RUS», which guarantees a significant reduction in defects, increased labor productivity and energy savings by 30–50 %.